Rasa, etniczność i religia w filipińskim procesie narodowotwórczym .......... 179 (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
RACE, ETHNICITY, AND RELIGION IN THE NATIONBUILDING PROCESS OF THE PHILIPPINESThis chapter aims to present the cultural mosaic that constitutes the Filipino society. It discusses linguistic and religious diversity, as well as the racial constructs functioning in the archipelago. The final section outlines nation-building processes and their limitations.